Ethene Conversion at a Zeolite‐Supported Ir(I) Complex.A Computational Perspective on a Single‐Site Catalyst System. Issue 15 (16th July 2021) - Vummaleti, Sai V. C.; Genest, Alexander; Rösch, Notker
Abstract : The Cover Feature illustrates that the product selectivity, ethane vs. butene, depends on the metal center, Ir vs. Rh, of a zeolite‐supported complex M(I). In their Full Paper, S. V. C. Vummaleti et al. model an Ir‐ethene complex located in a faujasite cavity by applying a quantum mechanics/molecular mechanics scheme involving DFT calculations. While most steps and barriers in the computed reaction network for Ir are rather similar to its Rh congener, the higher crucial C−C coupling barriers, by ∼50 kJ mol −1 relative to Rh, reverse the product selectivity from butene to ethane in the case of Ir. The center Ir(I) adsorbs ethene to form an active complex [Ir(C2 H4 )3 ] + /zeo that ultimately is able to activate hydrogen yielding ethane as main product, rationalizing the experiments. Both a Cossee‐Arlmann and a metallacycle mechanism were studied with the former one being most active via an in situ generated ethyl complex [Ir(C2 H4 )(C2 H5 )2 ] + /zeo. More information can be found in the Full Paper by S. V. C. Vummaleti et al.